Reversal of acute renal injury after peritoneal dialysis in a dog - Guiot, Êmille Gedoz [UNESP]; Guimarâes-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Chacar, Fernanda Chicharo [UNESP]; Gomide, Paula; Lourenço, Maria Lúcia Gomes [UNESP]; Melchert, Alessandra [UNESP] (My University, 2015)
Acute renal injury is characterized by a sudden injury in renal parenchyma that causes loss in its excretory, metabolic and endocrine function. The dialysis therapy has been instituted in the small animal clinic aimed at removing metabolic waste and correcting electrolyte disturbances of renal dysfunction. Peritoneal dialysis is a therapy based on the use of the peritoneum as a semi-permeable membrane through which there is exchange of solutes and fluid between blood from the peritoneal capillaries and the dialysis solution. We describe a case of acute kidney injury refractory to drug therapy in a canine female mixed-breed, with 13 years old. The patient was presenting anorexia, vomiting, decubitus and anuria, had a history of prolonged treatment with anti-infammatory drugs, was azotemic and in metabolic acidosis. Anuria persisted after drug therapy (volume restoration, chemical and osmotic diuresis and renal vasodilation) then starting to peritoneal dialysis (PD). Were performed three cycles of PD, during the second cycle patient left anuria and at the end of the third cycle showed clinical improvement, reduction of azotemia, hyperkalemia and metabolic acidosis. PD has shown satisfactory results, reversing the anuria, reducing azotemia and electrolyte disturbances, thereby providing clinical improvement.
Reversâo da injúria renal aguda após diálise peritoneal em câo
Keywords: Dialysis therapy; Renal dysfunction; Small animals